2012
DOI: 10.2144/000113964
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Nucleotide-Based Libraries Using Lambda Exonuclease

Abstract: Directed evolution of nucleotide libraries using recombination or mutagenesis is an important technique for customizing catalytic or biophysical traits of proteins. Conventional directed evolution methods, however, suffer from cumbersome digestion and ligation steps. Here, we describe a simple method to increase nucleotide diversity using single-stranded DNA (ssDNA) as a starting template. An initial PCR amplification using phosphorylated primers with overlapping regions followed by treatment with lambda exonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Transfer tubes/plate to thermal cycler and heat at 95°C for 30 sec, then immediately transfer to ice for 1 min. (Lim et al, 2012), or if template or primer is biotinylated, XNA can be isolated using streptavidin-coated magnetic beads (see Taylor & Holliger, 2015b); in this scenario, synthesis can be primed using RNA, which can subsequently be removed by alkaline hydrolysis].…”
Section: Methodsmentioning
confidence: 99%
“…Transfer tubes/plate to thermal cycler and heat at 95°C for 30 sec, then immediately transfer to ice for 1 min. (Lim et al, 2012), or if template or primer is biotinylated, XNA can be isolated using streptavidin-coated magnetic beads (see Taylor & Holliger, 2015b); in this scenario, synthesis can be primed using RNA, which can subsequently be removed by alkaline hydrolysis].…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, Klenow fragment is employed to create dsDNA. In this manner, site-specific mutagenesis can be performed using primers that contain degenerate bases [246].…”
Section: Enzyme-based Approachesmentioning
confidence: 99%
“…Apart from conventional directed evolution that relies on digestion and ligation, other enzymes with different functions can be utilized for mutagenesis. Lim et al reported the ability to carry out DNA shuffling using an ssDNA template and lambda exonuclease [186]. In nature, lambda exonuclease assists in DNA recombination of viral DNA.…”
Section: In Vitro Affinity Maturation Strategiesmentioning
confidence: 99%